Effects of Different Cotton Straw Returning Rates on Soil Physicochemical Properties and Cotton Growth - FANG Baihan; LI Yueyao; YANG Maoqi; GUO Xiaowen; YE Yang; GUO Huijuan; MIN Wei (Shuitu Baochi Xuebao)
［Objective］ Based on the rational utilization of cotton straw resources, this study studied the effects of different amounts of cotton straw returning on soil physicochemical properties, nitrate-nitrogen leaching, nutrient invertase activity and cotton growth, in order to provide a theoretical basis for soil fertility improvement and sustainable agriculture development in drip-irrigated cotton fields in arid areas. ［Methods］ Four treatments were set up, including no returning (CK), half returning of cotton straw (50%ST), full returning of cotton straw (100%ST), and double returning of cotton straw (200%ST). ［Results］ The proportion of large aggregates in soil was significantly increased by different rates of cotton straw returning to the field, and the increase under cotton straw returning to the field by 88.44% to 126.80% compared with no return. Meanwhile, cotton straw returning significantly increased the mean mass diameter and geometric mean diameter of aggregates, and enhanced the stability of aggregates. 50%ST, 100%ST and 200%ST significantly decreased soil bulk density, increased soil porosity and soil water content, compared with CK, with soil water content being increased by 22.83% to 42.06%. Cotton straw returning to the field significantly increased the contents of soil organic matter, total nitrogen, alkali-hydrolyzed nitrogen, available phosphorus and available potassium. Compared with CK, 100%ST and 200%ST significantly decreased nitrate-nitrogen leaching in the 0—100 cm soil. The activities of soil urease and alkaline protease were significantly increased with the increase of cotton straw returning rate.50%ST significantly increased cotton plant height, SPAD, Chl value, and dry matter weight. 50%ST, 100%ST, and 200%ST significantly increase the absorption of nitrogen, phosphorus, and potassium by cotton, thereby promoting the growth and development of cotton. Cotton straw returning significantly increased seed cotton yield by 4.61% to 12.59%, and nitrogen-use efficiency was significantly increased by 7.41% to 17.52%, compared with CK. ［Conclusion］ Cotton straw returning to the field can increase the proportion of large aggregates, reduce soil bulk density, increase soil porosity and water content, improve soil physical structure, and increase soil nutrient content, reduce nutrient leaching, thereby increasing the activities of soil nutrient convertases, promoting the growth and nutrient absorption of cotton, and improve the yield of seed cotton and nitrogen-utilization efficiency.